INOVASI PEMERINTAHAN DESA SUNGAI KALI MELALUI PEMANFAATAN TEKNOLOGI INFORMASI - , Farid Nofiard (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
Latent problems surrounding Human Resources and Information Technology Infrastructure are the main obstacles to the use of Information Technology in the innovation process of the Sungai Kali Village government. The paradigm